Evaluation of Fomitopsis betulina strains for growth on different media and exopolysaccharide production - Kizitska, Tetiana; Barshteyn, Viсtor; Sevindik, Mustafa; Krupodorova, Tetiana (Archives of Biological Sciences, 2024)
Paper description: Fomitopsis betulina fungus has valuable medicinal potential. We screened 22 different betulina strains for mycelial growth on different media and exopolysaccharide production. Growth in agar media was measured by radial growth rate, and growth in liquid media by biomass dry weight/L. The crude exopolysaccharide content was examined by the phenol-sulfuric acid method. The importance of growth media and fungal strains in the production of biomass and exopolysaccharides is shown. The study helps establish optimal protocols for cultivating betulina in laboratory and industrial settings. Abstract: Fomitopsis betulina is a widespread macromycete with valuable medicinal potential. This study screened 22 different F. betulina strains for mycelial growth on various media and exopolysaccharide production. Strain-specific features of F. betulina growth and exopolysaccharide production on different media were observed. Variations in the growth rate of the studied strains ranged from 3.50±0.33 to 8.75±0.50 mm/day, biomass synthesis from 2.28±0.26 to 13.72±0.05 g/L, and exopolysaccharide production from 0.02±0.00 to 2.20±0.31 g/L. Maltose as a carbon source in malt extract agar (MEA) and malt extract broth (MEB) was the most suitable for the growth, while dextrose and starch as carbon sources in potato dextrose broth (PDB) were more suitable for exopolysaccharide production. The F. betulina 311 strain has significant biotechnological potential, demonstrated by its robust growth on different agar media, efficient biomass synthesis, and high production of extracellular biopolymers. Our results highlight the significance of different growth media and fungal strains in optimizing biomass and exopolysaccharide production.